ANALYSIS OF PROBLEM SOLVING ABILITY BASED ON POLYA'S THEORY OF LAND CADETS IN APPLIED MATHEMATICS COURSE - Nurasiah, Lilis; Barr, Farah Dzil; Irianti, Nathasa Pramudita; Irsal, Nur Aliyyah; Shomad, Zahid Abdush (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
Purpose: This research aims to determine the initial problem solving ability of land cadets in applied mathematics courses. Methods: This research method is descriptive quantitative, where this method is taken to describe the condition situation with descriptive quantitative description. Abalysis: The research subjects were cadets of the D-IV Land study programme of the National Land College who took applied mathematics courses in the 2024/2025 academic year. The research data studied in this study are cadets' answer sheets on the pre-test. Result and discussion: From the results of the study, it was concluded that the problem solving ability of cadets was in the "very poor" category with the most dominant indicator of problem solving ability was the ability to plan problem solving, which was 74.62%. In addition, the indicators of problem-solving skills that are still lacking are indicators of understanding the problem, planning the problem, and indicators of checking back taken, which respectively have a mastery percentage of 16.5, 9.5% and 2% and 54.62%. Conclusion: With this we know the condition of students, weaknesses, strengths and what to do in order to improve problem solving skills.